Dooyeweerd's Understanding of Meaning (2): Some Implications - Basden, Andrew (Philosophia reformata, 2019)
Meaning is important in everyday life, and each science focuses on certain ways in which reality is meaningful. This article (the second of two) discusses practical implications of Herman Dooyeweerd's understanding of meaning for everyday experience, scientific theories, scientific methodology, and philosophical underpinning. It uses eight themes related to meaning in Dooyeweerd's philosophy, which are discussed philosophically in the first article (and summarised here). This article ends with a case study in which the themes are applied together to understanding Thomas Kuhn's notion of paradigms.